2006
DOI: 10.1007/s11090-006-9045-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature on Gas-Phase Toluene Decomposition in Plasma-Catalytic System

Abstract: The decomposition of toluene on c-alumina, MnO 2 -alumina and Ag 2 Oalumina catalysts in a plasma-catalytic reactor is tested. A comparison between catalytic, catalyst-after-plasma and catalyst-in-plasma systems is made in 150-400°C temperature range. An Arrhenius plot is made in order to deduce the mechanism of plasma activation. It was found that there is no difference between the measured activation energy for catalytic and catalyst-after-plasma systems. On the other hand it was found that plasma could acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 24 publications
1
54
0
Order By: Relevance
“…A similar result is also obtained with toluene and propane [9]. Demidyuk and Whitehead [10] studied the effect of temperature on the conversion of gas phase toluene. Magureanu et al [11] have studied effects of the temperature on the toluene conversion and the CO 2 yield in a dielectric barrier discharge (DBD) combined with Mnbased phosphate catalysts placed downstream of the plasma reactor, it is found that in the range of 0-400°C, both the conversion and the CO 2 yield increase with the temperature.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…A similar result is also obtained with toluene and propane [9]. Demidyuk and Whitehead [10] studied the effect of temperature on the conversion of gas phase toluene. Magureanu et al [11] have studied effects of the temperature on the toluene conversion and the CO 2 yield in a dielectric barrier discharge (DBD) combined with Mnbased phosphate catalysts placed downstream of the plasma reactor, it is found that in the range of 0-400°C, both the conversion and the CO 2 yield increase with the temperature.…”
Section: Introductionsupporting
confidence: 70%
“…There are a number of publications investigating the effect of gas temperature on the conversion of VOCs [8][9][10][11][12]. It is found that an increase of gas temperature is beneficial to CH 4 decomposition [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first work by Yamamoto et al [11], electron beams as well as several types of discharge such as dielectric barrier (DBD) or corona discharges, capillary discharge, DC glow discharge, multi hollow needle discharge, and also various types of packed-bed reactors, have been studied for the treatment of toluene in air [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Some results were published concerning the efficiency of the nitrogen plasma to remove toluene and about the influence of the oxygen percentage added to N 2 [15,19,23,24,29].…”
Section: Introductionmentioning
confidence: 99%
“…Another way in which information about the mechanism of plasma-assisted catalysis can be derived is to use the temperature-dependent data to extract kinetic information via an Arrhenius-type analysis. We have performed such an analysis for the destruction of toluene in an atmospheric-pressure air stream using thermal catalysis and plasma-assisted catalysis in both a one-and two-stage system [17]. The catalysts used were Ag/γ-Al 2 O 3 and Mn 2 O 3 /γ-Al 2 O 3 .…”
Section: Toluenementioning
confidence: 99%